Ketersediaan Koleksi Perpustakaan dalam Mendukung Kurikulum Merdeka Belajar Pada Bidang Penjaskesrek di Universitas Riau - Nurasmi; Evi Susanti; Nurhayati; Anton Yuliarto (Perpustakaan Universitas Riau, 2023)
College libraries have a crucial role in supporting the student learning process by providing high-quality reading materials that are in accordance with the curriculum. In essence, the library's main task is to develop a strong collection for the benefit of its users. Evaluation is one way to determine the suitability of a collection with the curriculum. The aim of this research is to evaluate the availability of collections to meet the need for reference materials in accordance with the Semester Program Plan (RPS) for the main courses in the Penjaskesrek Study Program FKIP Riau University, semester 1 to semester 6. This research uses a quantitative approach to calculate the percentage of availability of appropriate collections using the checklist method to measure and analyze the availability of teaching material collections, by checking and matching the library collection database as well as the main teaching materials contained in the RPS for Physical Education Study Program courses. The research results showed that of the 25 courses there were 121 collection titles listed in the RPS, and the results of the checklist carried out on the Riau University Library database were only available for 15 book titles or 12%. The conclusion of this research can be stated, the availability of the library collection of the Penjaskesrek Study Program FKIP Riau University does not fully meet the need for reference materials in accordance with the RPS, with only 12% of the appropriate book titles out of a total of 121 titles listed. Further attention and increased collections are needed to support the success of student learning in achieving curriculum goals.